Dakwah Kontemporer: Pengertian, Sejarah, Metode dan Media untuk Pengembangan Dakwah Kontemporer - Efendi, Erwan; Suseno, Heri; Harahap, Nisa Hanum (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
The existence of contemporary da'wah at this time needs to be brought closer to science, especially when facing current conflicts in society. Islam is a religion of rahmatan lil 'alamin, of course it must be able to provide donations and solutions in the development and change of modern society. So far, Islamic civilization has stagnated and even Islam has moved away from the hustle and bustle of the world of science. if we look back, Islam has actually been a pioneer of scientific findings that have been developed by Western civilization. Even though science and world civilization today, the focus is on Western civilization and it seems as if Islamic civilization will stagnate without significant progress for the benefit of the people. on the development model of mass communication media which indeed allows da'wah today to be conveyed simply, quickly and evenly Keywords: Da'wah, Media, Contemporary